MORPHOCLINICAL ASPECTS OF THE CLINICAL COURSE OF ATOPIC CHEILITIS - Hasiuk, N.V.; Yeroshenko, G.A.; Mochalov, I.O.; Klitynska, O.V.; Pogoretska, Kh.V. (World of Medicine and Biology, 2020)
The paper presents some clinical and morphological features and aspects of the clinical course of atopic cheilitis. The findings of comprehensive observations proved that clinical course of the disease have an impact on the nature of changes in the cellular composition of the vermilion border. The comprehensive analysis of the cytograms enables considering atopic cheilitis in the examined cohort, in the absence of adequate therapy, as a continuous self-destructive process. Its components (inflammatory-infiltrative and destructive) can regress under the influence of effective treatment and reactivate when the process is exacerbated under the influence of provoking factors, namely neurogenic and sensitizing. The findings of the study indicate the pathogenetic significance of destructive changes in epitheliocytes and violation of colonization resistance to the clinical course of atopic cheilitis.
Keywords: cheilitis; vermilion border; cells; nucleus; microflora